Non-natural amino acids - Muir, Tom W.; Abelson, John (Methods in enzymology ;, 2009)
By combining the tools of organic chemistry with those of physical biochemistry and cell biology, this title provides fundamental insights into how proteins work within the context of complex biological systems of biomedical interest.